On the uniform convergence of wavelet expansions of random processes from Orlicz spaces of random variables. I - Kozachenko, Yu. V.; Perestyuk, M. M. (Ukrains’kyi Matematychnyi Zhurnal, 2007)
We establish conditions under which there exists a function c(t) > 0 such that X (t)c(t) < ∞, where X(t) is a random process from an Orlicz space of random variables. We obtain estimates for the probabilities P{ X (t)c(t) > ε}, ε > 0..